Correlation of Body Mass Index with Lumbar Flexibility in Obese Students at HKBP Nommensen University Medan - Lamtiar, Rebecca Rumesty; Sibarani, Erwin Piter (Jurnal EduHealth, 2022)
The Body Mass Index (BMI) is a widely-used indicator to assess nutritional status in adults. An increase in BMI escalates the risk of diseases related to obesity. There has been a global rise in obesity, and numerous studies on the correlation between BMI and lumbar flexibility show significant relationships. Given the importance of lumbar flexibility in daily activities, this research explores the link between BMI and lumbar flexibility among obese students aged 18-21 at HKBP Nommensen University. An observational analytical study with a cross-sectional design was conducted on students from the Faculty of Medicine, spanning the batches from 2015 to 2018, excluding athletes and those with vertebral deformities or a history of chronic illness. Out of 50 male obese respondents at HKBP Nommensen University, Medan, the average lumbar flexibility was found to be 23.49 cm. A weak positive correlation was identified between BMI and lumbar flexibility with a Spearman correlation coefficient of 0.324. The results indicate that as BMI increases, lumbar flexibility also increases, although with a weak correlation strength. This contrasts with some previous studies, highlighting the unique nature of the sample population and the need for more comprehensive future research. For subsequent researchers, considering a larger sample size, different methodologies, or other factors influencing flexibility would be beneficial. although with a weak correlation strength. This contrasts with some previous studies, highlighting the unique nature of the sample population and the need for more comprehensive future research. For subsequent researchers, considering a larger sample size, different methodologies, or other factors influencing flexibility would be beneficial. although with a weak correlation strength. This contrasts with some previous studies, highlighting the unique nature of the sample population and the need for more comprehensive future research. For subsequent researchers, considering a larger sample size, different methodologies, or other factors influencing flexibility would be beneficial.